High Temporal Resolution Satellite Observations of Fire Radiative Power Reveal Link Between Fire Behavior and Aerosol and Gas Emissions. Issue 23 (5th December 2020) - Wiggins, Elizabeth B.; Soja, Amber J.; Gargulinski, Emily; Halliday, Hannah S.; Pierce, R. Bradley; Schmidt, Christopher C.; Nowak, John B.; DiGangi, Joshua P.; Diskin, Glenn S.; Katich, Joseph M.; Perring, Anne E.; Schwarz, Joshua P.; et al.
Abstract: Wildfire smoke influences on air quality and atmospheric chemistry have been underscored by the increasing fire prevalence in recent years, and yet, the connection between fire, smoke emissions, and the subsequent transformation of this smoke in the atmosphere remains poorly constrained. Toward improving these linkages, we present a new method for coupling high time‐resolution satellite observations of fire radiative power with in situ observations of smoke aerosols and trace gases. We apply this technique to 13 fire plumes comprehensively characterized during the recent FIREX‐AQ mission and show that changes in fire radiative power directly translate into changes in conserved smoke tracers (CO2, CO, and black carbon aerosol) observed in the downwind smoke plume. The correlation is particularly strong for CO2 (mean r  > 0.9). This method is important for untangling the competing effects of changing fire behavior versus the influence of dilution and atmospheric processing on the downwind evolution of measured smoke properties. Key Points: Geostationary satellite observations of fire radiative power are highly correlated with in situ airborne measurements of primary‐emission smoke tracers High‐resolution satellite observations are needed to disentangle how fire activity and plume dilution impact the downwind evolution of smoke Diurnal fire activity for wildfires observed during FIREX‐AQ is best parameterized using a bimodal Gaussian distribution to inform models